Pendampingan Pembuatan Konten Instagram Sebagai Strategi Digital Marketing UMKM Di Kelurahan Keputih - Damayanti, Ella Alma; Sibarani, Steven Arrow Rinel; Maulana, Fikih; Febrianita, Roziana (Lembaga Penelitian, Pengabdian kepada Masyarakat dan Publikasi Universitas Bhayangkara Jakarta Raya, 2022)
In accordance with the activities with the theme of training and mentoring in the creation of Instagram content, it intends to channel and develop the skills of entrepreneurs in the Keputih village in the digital era. This training and assistance use skilled techniques in terms of marketing in the field of copywriting which aims to attract consumers to buy these products, in addition to good and correct copywriting techniques, of course, photographic techniques are needed for the aesthetic power of these products, in training and assistance in taking photos. the product must be considered in terms of angle and light capture, besides the media that will be used for taking product photos must be considered, the mini studio is one of the supporting parts for product photos, this material is easy to find in everyday life, for example, a mini studio that made of cardboard used for mineral water, in addition to materials that are easy to shape, used cardboard is an affordable and practical material, so there is no need to inflate costs, other supporting media are asturo paper, oil paper which will be pasted on the outside and inside of the cardboard the. The results of the research from the discussion indicate that copywriting techniques and supporting photography techniques are skills that must be possessed by entrepreneurs who want to start businesses so that they can attract the attention of consumers.